(untitled) (Journal of Oriental Studies, 2016)
There is the research of the activity of mosques and medresses and of the level of the religious activity of the population in the end of the 20th – the beginning of the 21 centuries in the Karaganda region and Pavlodar city (based on the fi eld data of the author) in the focus of this article. The attention is paid to the religious education of the Muslim clergy that time, their enlightening activity among believers. These ethnographic materials allowed us to see the picture of religious activity of the urban and the rural population. That time there was observed the tendency of increasing of the level of the Muslim clergy’s religious education, opening of new medresses and Islamic courses not only for the clergy but for everyone: for the children and the old people who wished to obtain religious knowledge.